2019
DOI: 10.1080/02615479.2019.1663812
|View full text |Cite
|
Sign up to set email alerts
|

The role of critical social work education in improving ethical practice with refugees and asylum seekers

Abstract: This paper uses critical reflection as its primary methodology to research one Master of Social Work student's former practice experiences as an Australian immigration officer. The paper contextualizes the study by offering a critical analysis of hegemonic constructions of asylum seekers in Australia, which are reflected in Australian law and policy, as well as potentially influencing social work practice. Critical reflection on one of the author's practice provides a rich case study that reveals the tensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The findings suggest using supervision informed by critical reflection would be effective in supporting practitioners to resist neoliberalism so that practice remains ethical and centred on service users (O'Leary et al 2013;Reimer 2014). Several critical scholars have also demonstrated social workers can and do use critical reflection and critical analysis as part of a strategic approach to work successfully with services users in an ethical manner (see for example, Morley et al 2019a;Morley and Stenhouse 2020;Mueller and Morley 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggest using supervision informed by critical reflection would be effective in supporting practitioners to resist neoliberalism so that practice remains ethical and centred on service users (O'Leary et al 2013;Reimer 2014). Several critical scholars have also demonstrated social workers can and do use critical reflection and critical analysis as part of a strategic approach to work successfully with services users in an ethical manner (see for example, Morley et al 2019a;Morley and Stenhouse 2020;Mueller and Morley 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other research using Fook's model ( 2016) argues that critical reflection can address the disparity and tension between ethical, socially just practice, and technical competence according to organisations (Morley et al 2019a). Elsewhere, it is suggested Fook's model of critical reflection provides the intellectual spaces required for practitioners to think beyond dominant constructions of professional practice as defined by neoliberalism (Morley and Stenhouse 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given the identified gap between practitioner's intentions to meaningfully include children's voices in practice, critical reflection was employed as both a research and educational strategy as it has been shown to effectively transform practice and address issues that concern both organisations and practitioners (see for example, [46,[51][52][53][54][55][56]).…”
Section: Methodsmentioning
confidence: 99%
“…As a research methodology, critical reflection fortifies the link between research, theory, knowledge, and practice [51,57] by enlisting the research participants as co-inquirers [58] to generate effective practice strategies [46,51,[53][54][55][56]. In this research, critical reflection is being used to address the difficulties identified in implementing child-inclusive intentions into practice.…”
Section: Methodsmentioning
confidence: 99%
“…However, the ultimate moral injury may be that without critical training some HPs adopt official language and worldviews, becoming insensible to the social justice issues (Morley et al, 2019). They may regard detainees' disorders and self-harm as "detention fatigue" or learned behaviour, allegedly fostered by refugee advocates to secure claim acceptance (Immigration Minister Dutton, quoted by Lewis, 2019); or question immigrants' morality while representing themselves as engaging in "caring control" (Vega, 2018).…”
Section: Arguments For Health Professionals Boycotting Immigration Detentionmentioning
confidence: 99%